Simultaneous Determination of Paracetamol and Diclofenac Sodium from Combined Dosage Forms by Absorbance Difference Method - Jaleel Saheb, D.; Rami Reddy, N.; Chakravarthy, I.E. (Asian Journal of Chemistry, 2016)
A new spectrophotometric method for the simultaneous and separate estimation of paracetamol and diclofenac sodium in binary tablet formulations has been described. The method is based on the estimation of one drug in presence of another drug by absorbance difference method. The paracetamol and diclofenac sodium solutions were scanned over the range of 210 to 304 run. In this method, two wavelengths 230 and 254 run were chosen for paracetamol; at these wavelengths the absorbance was almost zero and in case of diclofenac sodium it should be considerable absorbance difference. Similarly the two wavelengths 260 and 292 run were chosen for diclofenac sodium; at these two wavelengths absorbance difference was almost zero and it should be considerable absorbance difference in case of paracetamol. In the mixture of paracetamol and diclofenac sodium solution the absorbance values of four wavelengths 260, 292, 230 and 254 run were measured. The amount of paracetamol is directly proportional to the absorbance difference between 230 and 254 nm. Similarly the amount of diclofenac sodium is directly proportional to the absorbance difference between 260 and 292 nm.